2016
DOI: 10.1002/anie.201604321
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Partially Protected Nonsymmetric Biphenols by Reagent‐ and Metal‐Free Anodic Cross‐Coupling Reaction

Abstract: The oxidative cross-coupling of aromatic substrates without the necessity of leaving groups or catalysts is described. The selective formation of partially protected nonsymmetric 2,2'-biphenols via electroorganic synthesis was accomplished with a high yield of isolated product. Since electric current is employed as the terminal oxidant, the reaction is reagent-free; no reagent waste is generated as only electrons are involved. The reaction is conducted in an undivided cell, and is suitable for scale-up and inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
0
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 160 publications
(97 citation statements)
references
References 58 publications
1
76
0
20
Order By: Relevance
“…using chemical oxidizers demonstrated that this electrochemical cross-coupling can easily compete with conventional methods. [109] Recent studies have highlighted its robustness, [111] and extended the applicability of this process to the electrochemical synthesis of partially protected non-symmetric biphenols, [112] protected bianiline derivatives [113] (Scheme 34, top), and m-terphenyl-2,2''-diols by twofold CÀCc ross-coupling [114] (Scheme 34, bottom). Thec rosscoupling of phenols with heterocycles was recently described.…”
Section: Anodic Couplings By Càha Ctivationmentioning
confidence: 99%
See 1 more Smart Citation
“…using chemical oxidizers demonstrated that this electrochemical cross-coupling can easily compete with conventional methods. [109] Recent studies have highlighted its robustness, [111] and extended the applicability of this process to the electrochemical synthesis of partially protected non-symmetric biphenols, [112] protected bianiline derivatives [113] (Scheme 34, top), and m-terphenyl-2,2''-diols by twofold CÀCc ross-coupling [114] (Scheme 34, bottom). Thec rosscoupling of phenols with heterocycles was recently described.…”
Section: Anodic Couplings By Càha Ctivationmentioning
confidence: 99%
“…Various electrochemical cross-couplings enabled by CÀH activation developed by Waldvogel and co-workers. [107][108][109][110][111][112][113][114] Scheme 35. General cyclization of olefins with trapping nucleophiles.…”
Section: Electrochemical Synthesis Of Heterocyclesmentioning
confidence: 99%
“…[9,10] Die Anwendung dieser Strategien ist oft mit großem Aufwand und komplizierten Reaktionsbedingungen verbunden. [15] In unserer Gruppe wurden die anodische Phenol-Phenol- [12,16,17] sowie die Phenol-Aren-Kreuzkupplung entwickelt. [11,12] Kürzlich wurde eine Arbeit über die oxidative Umsetzung von Diarylaminen mittels eines hochfluorierten Eisen-Phthalocyanin-Katalysators,d er sowohl C-C-als auch N-N-Kupplungen ermçglicht, verçffentlicht.…”
unclassified
“…Diese Untersuchungen haben gezeigt, dass eine Elektrolysetemperatur von 30 8 8Cv orteilhaft ist (Nr.3und 6). [16] Wire rreichten die selektive Abspaltung einer Boc-Gruppe durch Wasser ohne die Notwendigkeit zusätzlicher Säure, [29] während die Acetyl-bzw.B enzoylgruppe in den Substraten 4 und 6 verblieben (Tabelle 3, Nr.1und 2). Die genutzten Schutzgruppen basieren auf gebräuchlichen Carbonsäuren und kçnnen daher einfach durch Standardmethoden entfernt werden.…”
unclassified
“…Eine elegante Reaktionsführung,d ie dieses Problem umgeht, wurde von Yoshida und Mitarbeitern mit der Cation-Pool-Methode entwickelt. [23,28] Die Bildung reaktiver Intermediate mittels Elektrolyse ist unter atomçkonomischen und kostentechnischen Aspekten äußerst vielversprechend. Die Anwendung dieser Methode hinsichtlich Schwefelheterocyclen wurde durch die Kupplung von Naphthalin mit 2-Iodbenzothiophen an einem Beispiel demonstriert.…”
unclassified